Evaluation of the BioPlex 2200 Syphilis System as a First-Line Method of Reverse-Sequence Screening for Syphilis Diagnosis - Marangoni, Antonella (American Society for Microbiology, 2013)
Despite recent technological advances, the diagnosis of syphilis remains a challenging enterprise. Actually, most high-volume laboratories have adopted the “reverse algorithm” due several factors, including the potential to automate testing. Recently, immunoassays processed on random-access systems have been proposed as screening tests. The purpose of this study was to evaluate diagnostic performances of BioPlex 2200 Syphilis IgG and BioPlex 2200 Syphilis IgM, tests based on Multiplex Flow technology, in comparison with the performance of Architect Syphilis TP, a chemiluminescent immunoassay for the detection of IgG and/or IgM anti-Treponema pallidum antibodies. A retrospective study was performed with a panel of 100 blood donor sera, a panel of 350 clinical and laboratory-characterized syphilitic sera, and 170 samples obtained from subjects with potentially interfering conditions. Moreover, 200 unselected samples submitted to the Microbiology Laboratory of St. Orsola Hospital in Bologna for routine screening for syphilis were evaluated. As confirmatory tests, T. pallidum hemagglutination and Western blot assays were used. Considering the IgG Western blot (WB) assay to be the gold standard method, BioPlex 2200 Syphilis IgG specificity was far higher than Architect Syphilis TP specificity (89.7% versus 78.4%, respectively), whereas the sensitivity was 100% for both automated methods. Compared to the IgM WB assay, BioPlex 2200 Syphilis IgM performed with a specificity of 94.9%, whereas the sensitivity was 84.8%. Considering the excellent ease of use and automation, the high sample throughput and its valuable analytical performances, BioPlex Syphilis 2200 IgG could represent a suitable choice for high-volume laboratories. BioPlex Syphilis 2200 IgM could be considered a good addition to IgG testing for uncovering active infections.